Transferring motivation from educational to extramural contexts: A review of the trans-contextual model - Hagger, Martin; Chatzisarantis, N.L.D. (Springer, 2012)
A key question for educators is whether teaching styles, methods, and practices not only foster motivation toward, and persistence with, learning activities in the classroom but also in contexts outside of school (Ciani et al. 2010). There is a wealth of evidence in the social psychological literature applied to educational contexts that has indicated that teaching styles and other motivational strategies adopted by social agents like teachers and educators lead to adaptive outcomes within the school context. For example, adopting democratic teaching styles (Tomasetto 2004), fostering mastery oriented motivational climates (Barkoukis et al. 2008), and providing autonomy support (Reeve 2002) are strategies that have been utilised by social agents in educational contexts to promote increased motivation among pupils and students. Overall, the support offered by teachers in the classroom has been shown to have direct effects on pupils’ emotional and motivational responses (e.g. Covington and Dray 2002). Furthermore, the adoption of autonomy-supportive strategies has been associated with numerous adaptive outcomes such as academic achievement (Deci et al. 1991), perceived competence (Harter 1985), deep learning of concepts (Lau et al.2008), and selection of tasks of optimal challenge (Murphy and Thomas 2008). There is also some evidence that such strategies also foster desirable outcomes beyond the classroom, such as engagement in extra-curricular activities (Tomasetto 2004) and studying behaviour (Kolic-Vehovec et al. 2008). This indicates that social agents’ behaviours in educational settings may motivate students to engage in behaviours and activities outside of school that are adaptive in terms of learning and skill development. Such influences likely fulfil a key goal of education to influence educational activities beyond the classroom.In addition, motivating students outside of the classroom will meet educational aims to promote increased transformative experiences (Pugh et al. 2010) and inquisitive behaviours (Yoon 2009) among pupils that assist in the development of flexible, critical, and analytic thinking skills that are generalizable and transferable. It must, however, be stressed that little is known of the processes by which teacher behaviours in educational contexts impact on students motivation and behaviour within the school and, most importantly, outside school. The aim of the present review is to provide an overview of a recently developed motivational model that outlines the processes by which perceptions of social agents’ behaviours that support motivation and learning affect motivation to engage in educational activities in both the classroom and extramural contexts. The model is based on the integration of leading social psychological and motivational theories and not only identifies the important factors and processes involved in trans-contextual motivation, but also provides an impetus for the development of interventions to promote motivation for learning activities in both educational and extramural contexts. After outlining the conceptual and theoretical bases of the model, we review a series of prospective and intervention studies from our laboratory that provides evidence to support its core trans-contextual premises. We also outline how the model serves as a novel basis for educational interventions to enhance motivation among pupils in educational and extramural contexts and the potential of the model to be applied to interventions in diverse educational contexts to promote general educational aims of fostering adaptive outcomes in students outside the classroom.